Developing pathways for modern and sustainable agriculture in emerging economies: investigating the impact of information and communication technology adoption on food security - Chandio, Abbas Ali; Alnafissa, Mohamad; Awan, Ashar; Haouas, Ilham; Doganalp, Nihat (Frontiers in Sustainable Food Systems, 2025)
This study examines the impact of information and communication technology (ICT) adoption on food security in emerging seven countries: namely China, India, Indonesia, Russia, Mexico, Brazil, and Turkey from 1995 to 2019. To obtain robust findings, we deploy several econometric approaches, including the Westerlund ECM co-integration test, PMG method, and D-H causality test. This research paper presents significant findings through the utilization of panel co-integration tests as the primary estimation techniques. The findings from the PMG method reveal that increases in usage of Mobile phone and Internet access significantly boost long-term food security by 0.092 and 0.036%, respectively. In addition, the findings from the Dumitrescy–Hurlin causal relationship test show a bidirectional causal relationship between Mobile phone use and food security but a unidirectional causality from Internet use to food security. Furthermore, the impact of ICT on food security is more prominent in the long run than in the short run. The current study’s conclusions have significant policy implications for the E7 countries. For example, the E7 countries should invest in ICT to gain future benefits. Authorities in the countries should develop and implement policies that encourage Mobile phone and Internet use in rural areas. Such a promotion will strengthen the farming system while also increasing sustainable food production.